Isolation, chemical and microbiological characterization of essential oils from tobacco waste - Kalamanda, Obrenija (Economics of Agriculture, 2010)
For the purpose of this investigation, the isolation, chemical and microbiological characterization of essential oils originate from tobacco waste were performed. The subjected tobacco waste was collected during the primary processing and cigarette making process in Tobacco Factory Banja Luka. In extracted essential oils 26 components where identified, as well in petrol ether extract (26 compounds). The major identified compounds of essential oil are Neophytadiene, Phtalic acid, Palmitic acid, Miristic acid and Epoxy labdenol. The microbiological activity examination was showed significant antibacterial affection of extracted essential oils and petrol ether extract on Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa.